Lyrics in the Poetry of Ahmad Shawqi - Al-Rifai, Nada Yousuf (Advances in Social Sciences Research Journal, 2018)
Ahmad Shawqi (1868-1932), "The Prince of Poets," did not leave any section of poetry without writing in it, in the same excellence and quality, whether in the field of description, pride, wisdom, philosophy, congratulation, praise, or lament. Shawqi even wrote simplified children's poetry, which included wisdom, love, and humanity. Shawqi was given opportunities which were unavailable to other poets of his time. He got a scholarship to France where he studied literature and law. There he had the chance to see the theater and to be connected with senior poets in other cultures, such as Hugo, Racine, and de Musset, in addition to his Turkish culture. Shawqi's Arabic and Western culture gave him access to many forms of literature, whether Arabic or Western, and he was introduced to great poets and intellectuals through their books and works. Shawqi's poetry was distinguished by its particular music, which was felt by the recipient through its letters, structure, rhythm, and rhyme. The opening verses of his poems were luxuriously tuning, in addition to a fine linguistic sense. This extravaganza of music associated with sweetness and craftsmanship is found only in Shawqi's poetry. Shawqi turned to the animal world to narrate stories in the tongues of the animals. He began in this genre when he was a student in France; as an artistic means to express his moral, national, and social desires and to awaken among the citizens a tragic feeling against colonialism and its machinations. Shawqi composed these tales in an easy and attractive manner. He narrated 56 of those tales, the first of which was published in the newspaper "Al-Ahram" in 1892, and was entitled "Al-Deek Al-Hindi wa Al-Dajaj Al-Baladi" (The Indian Rooster and the Local Chicken), and symbolized the occupying forces and Egypt. It is possible, in some ways, to consider Shawqi "The Prince of Poets," as Abdel Wahab's poet, since he has specially written for him colloquially sung poems like "Al-Neel Najashi," (The Nile is Negus), except that Shawqi initially wrote poetry for reading, and not for singing. From among this poetry, Abdel Wahab chose and sang many poems such as “Operetta Qais and Leila” with Asmahan, “Mount Al-Towbad,” “O Neighbor of the Valley,” “ I am Antonio,” and many other beautiful poems that granted Abdel Wahab fame and immortality. Umm Kulthum also sang some of Shawqi's immortal masterpieces like "Wuleda Al-Huda" (The Guide Mohammad is born), "Reemun ala alqa3” (A white antelope on the plain), "The Nile," and "Salu ku'ous al-tela" (ask the drizzling cups), and other poems that will never be worn out by time.